Scp160p associates with specific mRNAs in yeast - Li, Ai-Min (Oxford University Press, 2003)
Scp160p is a multiple KH-domain RNA-binding protein in yeast that has been demonstrated previously to associate with both soluble and membrane-bound polyribosomes as an mRNP component. One key question that has remained unanswered, however, is whether the mRNAs in these mRNP complexes are random or specific. We have addressed this question using microarray analyses of RNAs released from affinity isolated Scp160p-containing complexes, compared with total RNA controls from the same lysates. Our results, confirmed by quantitative RT–PCR analysis, clearly demonstrate that Scp160p associates with specific rather than with random messages, and that among the enriched targets are DHH1, YOR338W, BIK1, YOL155C and NAM8. Furthermore, loss of Scp160p resulted in a significant change in both the abundance and distribution between soluble and membrane-associated fractions for at least one of these messages (YOR338W), and in a subtle yet significant shift from soluble polyribosomes to soluble mRNPs for at least two of these target messages (DHH1 and YOR338W). Together, these data not only identify specific mRNA targets associated with Scp160p in vivo, they demonstrate that the association of Scp160p with these messages is biologically relevant.